PENGARUH KARAKTERISTIK DAN TATA KELOLA PERUSAHAAN TERHADAP TINGKAT PENGUNGKAPAN INFORMASI KEUANGAN DAN NONKEUANGAN MELALUI WEBSITE PERUSAHAAN DI INDONESIA - Dipo Rizkika Alfaiz; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2013)
The rapid development of the Internet creates a new way for companies to communicate with their stakeholders. One way that can be used is to disclose financial and non-financial information through the company's website, so the stakeholders can quickly and easily access them from anywhere and can immediately take a decision, especially investment. Complete information and detail can make investment decisions more effective, because it will be known to the performance and prospects of the company in detail. The research was conducted to analyze the effect of firm size, solvency, liquidity, industry type, ownership dispersion, the size of the board and audit committee size on the level of financial and non-financial disclosure through the company's website in Indonesia. The samples used in this research are 66 non-financial companies listed at Indonesia Stock Exchange in 2011. The conclusion that can be drawn from this study is the variable firm size, solvency, liquidity and dispersion of ownership have significant and positive impact on the level of financial and non-financial disclosure through the company's website in Indonesia, while other variables did not prove significant.